CONTRIBUTION BOARDING SCHOOLS FOR SOCIAL CHANGES IN CENTRAL JAVA INDONESIA - Shobron, Sudarno; Jinan, Mutohharun; Santoso, MA Fattah; Muthoifin; Santoso, Agus (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to discover the history of Imam Bukhari Boarding School from the early establishment and the further development, and the contribution of Imam Bukhari Boarding School in the term of Islamic da’wah movement particularly in Karanganyar Central Java. The objectives of the study are first to describe the early stage of Imam Bukhari establishment, the further development, the steps which were taken, the activity which is done in Imam Bukhari Boarding School. Second, to explain the contribution that Ma’had Imam Bukhari has done in the term of Islamic da’wah particularly in Central Java. The method applied in this study is descriptive qualitative method. The data were taken directly from Imam Bukhari Boarding School as the main source. The sources of the data are the policy holder, the founders of Imam Bukhari, secretary and officers of da’wah division of Imam Bukhari boarding school, secretariat division, administration officers, the teachers of the boarding school, and community leaders of Central Java. The data are collected through observation, interview and documentation, which are analyzed using descriptive qualitative method. It covers explaning and reducing the data, and finally makes the conclusion. The results of the study show that Imam Bukhari Boarding School is formed as an educational institution which applies comprehensive Islamic boarding school concept, the method of as Salaf, and Khalafi management concept. There are several stages of development that have been done. The stages could be divided into three stages, the establishment, developing and sustaining period. Now, Imam Bukhari is known as one of the best boarding school in Indonesia and reference for other schools. Imam Bukhari Boarding School also has great contribution in Islamic da’wah particularly in Central Java. The development of Islamic da’wah in Selokaton-Karanganyar has wider and better progress with the effort of the preachers who are also the teacher of Imam Bukhari. A good communication has been made between the civitas of Imam Bukhari, community leaders and religious leaders in Central Java.